2019
DOI: 10.3171/2018.10.jns182154
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned in the evolution of endoscopic skull base surgery

Abstract: OBJECTIVEEndoscopic skull base surgery (ESBS) is a relatively recent addition to the neurosurgical armamentarium. As with many new approaches, there has been significant controversy regarding its value compared with more traditional approaches to ventral skull base pathology. Although early enthusiasm for new approaches that appear less invasive is usually high, these new techniques require rigorous study to ensure that widespread implementation is in the best interest of patients.METHODSThe authors compared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 89 publications
1
37
0
1
Order By: Relevance
“…Numerous studies comparing EEA to transcranial surgery have demonstrated that in experienced hands, EEA can offer high rates of resection with low complications. 35 However, even after hundreds of cases, there are subtle changes in practice that indicate how the field is evolving. For example, our CSF leak rate was fairly constant and did not markedly improve over time, although our use of lumbar drains decreased.…”
Section: Evolution Of Skull Base Closurementioning
confidence: 99%
“…Numerous studies comparing EEA to transcranial surgery have demonstrated that in experienced hands, EEA can offer high rates of resection with low complications. 35 However, even after hundreds of cases, there are subtle changes in practice that indicate how the field is evolving. For example, our CSF leak rate was fairly constant and did not markedly improve over time, although our use of lumbar drains decreased.…”
Section: Evolution Of Skull Base Closurementioning
confidence: 99%
“…Therefore, the reconstruction of the skull base following extended EEA to the skull base is of paramount importance in avoiding post-operative CSF leak. Advances in skull base reconstruction, particularly the use of vascularized local flaps, have greatly reduced the incidence of this complication and have been instrumental in the expansion of these approaches for the management of skull base malignancy (25). The importance of using vascularized flaps as part of a multi-layer, rather than a monolayer closure of skull base defects to prevent post-operative CSF leak has also been highlighted in a recent study by Simal-Julián et al (26).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, skull base surgery has been modified in an attempt to make it less morbid [ 28 - 29 ]. Tailored AC aims to provide adequate exposure with less risk of neurovascular injury, allowing enough space to safely treat parasellar lesions.…”
Section: Discussionmentioning
confidence: 99%